Heat transfer characteristics during flow along horizontal and vertical minichannels. (April 2021) - Piasecka, Magdalena; Strąk, Kinga; Maciejewska, Beata
Highlights: Steady-state flow boiling heat transfer in horizontal and vertical minichannels. Several refrigerants, enhanced heated plate surface, flow patterns. Inverse heat conduction problem solved by FEM based on Trefftz functions. Comparison between experimental and predicted Nusselt numbers. New correlation for saturated flow boiling heat transfer in minichannels. Abstract: This work focuses on boiling heat transfer studies during cooling liquids flow (FC-72, HFE-649, HFE-7000 or HFE-7100) along a single minichannel of 1.7 mm depth, vertically or horizontally oriented. The temperature of the outer smooth side of the plate was measured by infrared thermography. The observations of the flow structures were carried out on the enhanced side of the plate contacting fluid. The heat transfer coefficient (HTC) on the enhanced plate–fluid contact surface was computed from the Robin boundary condition. The inverse heat conduction problem in the heated wall was solved by the Finite Element Method with the shape functions based on the Hermite interpolation and the Trefftz functions. The results were presented as relationships between HTC and the spatial variable referred to the flow direction at subcooled and saturated boiling and as boiling curves. Mean relative errors of HTC were determined. Two-phase flow patterns were shown and discussed. Selected correlations for boiling heat transfer have been used in calculations for comparison between experimental and predicted Nusselt numbers. The smallest mean absolute percentage error of the Nusselt number was achieved for Mikielewicz J. correlation at subcooled boiling. At saturated boiling no satisfactory results were achieved. Therefore, own correlation was proposed.